Optimalization of Load Balancing using Fuzzy Logic to Power Lost Costs in a 1 MVA Transformer - Liliana, Liliana; Ullah, Aulia; Aini, Zulfatri (Faculty of Engineering, Universitas Tanjungpura, 2025)
The 1 MVA transformer at UIN Suska Riau has experienced severe load imbalance, resulting in significant power losses, excessive neutral current, and reduced efficiency that accelerates insulation degradation and shortens its service life. Unlike previous studies that mainly focused on static phase balancing or software-based estimations, this research introduces a real-time load balancing strategy using Fuzzy Logic and projects power loss costs over 10 years. Real-time current measurements were collected over eight consecutive days under peak load conditions and processed through a MATLAB-based Fuzzy Logic system employing triangular membership functions and expert-defined inference rules. The research methodology includes load balancing, calculation of power losses and operational costs, and a comparison of pre- and post-balancing conditions. The results indicate a 95.58% reduction in load imbalance and more than 90% decrease in power losses. Furthermore, the 10-year projection analysis shows long-term operational cost savings of up to 99.65%, while the method also contributes to extending transformer lifetime by preventing overheating and insulation deterioration. The proposed approach enables utilities to mitigate neutral current, reduce energy losses, and lower operating costs across distribution networks.